The perceptions of students, the hospitality and tourism industry, and tourism polytechnics on internships during the COVID-19 pandemic - Ni Made Suastini; Ni Nyoman Sukerti; Irene Hanna H. Sihoming; I Gusti Agung Made Wirautama (Global Business & Finance Review (GBFR), 2022)
Purpose: The focus of the study is to identify the perceptions of the students, the hospitality and tourism organizations, and the tourism polytechnic concerning the internships conducted during the COVID-19 pandemic, as well as their perceptions of virtual internships. Design/methodology/approach: A survey method was used to collect the research data. Respondents comprised students from the six State Tourism Polytechnics (Perguruan Tinggi Negeri Pariwisata-PTNP), hospitality and tourism organizations, and the faculty internship coordinator & officials of each tourism polytechnics. Findings: The findings of the study indicated that the internship variables (student-focused issues, institution-specific issues, and organization-specific issues) were generally regarded as positive by the students, the hospitality and tourism organizations, and the tourism polytechnics. However, they all disagree on the issue of remuneration during the internship. There are seven items on which only PTNP stakeholders disagree, all of which pertain to the virtual internships variable. Research limitations/implications: The objective of the study is to enhance tourism and hospitality higher education internships in the new normal era through collaboration and internship creation aligned with industry demands. The study's respondents were primarily from Politeknik Pariwisata Bali (Bali Tourism Polytechnic), who generally presented a general image of Bali's diminishing tourism, which affected the internship program. Additional research should be conducted with a broader scope to allow for generalization findings. Originality/value: The study is highlighting the internships implementation during the COVID-19 pandemic, as well to explore the possibility if internships are carried out virtually.
Keywords: 650; Hospitality and tourism education; Internship; COVID-19 pandemic; Virtual internship; Perceptions